Sign problem of the fermionic shadow wave function - Calcavecchia, Francesco; Pederiva, Francesco; Kalos, Malvin H.; Kühne, Thomas D. (Physical Review E - Statistical, Nonlinear, and Soft Matter Physics, 2014)
We present a whole series of methods to alleviate the sign problem of the fermionic shadow wave function in the context of variational Monte Carlo. The effectiveness of our techniques is demonstrated on liquid He3. We found that although the variance is reduced, the gain in efficiency is restricted by the increased computational cost. Yet, this development not only extends the scope of the fermionic shadow wave function, but also facilitates highly accurate quantum Monte Carlo simulations previously thought not feasible.
CRIS-Team Scopus Importer:2023-03-20